2016
DOI: 10.1016/j.ejvs.2016.07.084
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Outcomes Following Aneurysm Repair in Patients with Synchronous Intra-abdominal Malignancy

Abstract: What this study adds to the existing literature and how it will influence future clinical practice 22The aim of this study was to determine outcomes in patients undergoing abdominal aortic aneurysm 23 (AAA) repair [endovascular (EVAR) or open] who have a synchronous malignancy. Synchronous intra-24 abdominal cancer is relatively common in patients undergoing AAA-repair and surgeons are faced with 25the dilemmas of what type of repair to offer and in what sequence. Our findings support that EVAR is 26 superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Many studies have analyzed the effect of AAA repair in patients with synchronous malignancy and showed increased short-term mortality and morbidity after both endovascular aortic repair (EVAR) and open surgical repair (OSR) [3]. In addition, patients with intra-abdominal tumors have increased perioperative mortality after OSR of AAA, and the history of intra-abdominal procedures may hinder OSR due to the development of adhesions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have analyzed the effect of AAA repair in patients with synchronous malignancy and showed increased short-term mortality and morbidity after both endovascular aortic repair (EVAR) and open surgical repair (OSR) [3]. In addition, patients with intra-abdominal tumors have increased perioperative mortality after OSR of AAA, and the history of intra-abdominal procedures may hinder OSR due to the development of adhesions [4].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with this, if the IRM is dealt with in the second stage, and complications arise after the first AAA operation, the interval between operations may be extended incommensurately and there may occur progress with possible generalisation of IRM. These are primarily tumours in higher TNM stage (9). Further possible advantages of an one-stage procedure include resolution of both diseases during a single operation, under general anaesthesia only once.…”
Section: Discussionmentioning
confidence: 99%
“…8) Furthermore, several studies have reported that EVAR is more advantageous than open repair in patients with synchronous intra-abdominal malignancy. 9) Considering these reports, endovascular repair provides an effective and alternative approach in a situation when conventional open repair may be hazardous or impossible. 10) We also chose EVAR considering the possibility of a tight adhesion between the aorta and lymphoid tissues; consequently, we had a good success.…”
Section: Discussionmentioning
confidence: 99%